Kepemimpinan Transformasional Kepala Madrasah dalam Pengembangan Program Tahfidz - Ambarawadi, Ndanda; Mutohar, Prim Masrokan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the transformational leadership of the madrasah head in developing a superior tahfidz program at MTs Unggulan Perwanida, Blitar City. The research is motivated by the importance of the madrasah head's role in building a culture of tahfidz discipline through a system of memorization targets, supervision, and continuous program evaluation. A qualitative approach with a case study design was employed. Data collection techniques included observation, in-depth interviews, and documentation. Informants included the madrasah head, tahfidz teachers, the vice principal, students, and parents. Data were analyzed using the Miles, Huberman, and Saldaña model, while data validity was tested through source and technique triangulation. The results showed that the madrasah head applied transformational leadership through role modeling, motivation, supervision, and regular evaluation of the tahfidz program. Development strategies included annual memorization targets, routine muroja'ah (revision), memorization monitoring, and the use of rewards and punishments. The program's success was supported by the commitment of the madrasah head, the competence of tahfidz teachers, and parental involvement in supervising students' memorization. Inhibiting factors included differences in students' memorization abilities, lack of consistency in muroja'ah, and time limitations. The study concludes that the transformational leadership of the madrasah head plays a strategic role in building a quality culture and discipline within the superior tahfidz program at Islamic educational institutions.